Evidence for aldosterone‐dependent growth of renal cell carcinoma. Issue 4 (7th May 2014) - King, Sharon; Bray, Susan; Galbraith, Sarah; Christie, Lesley; Fleming, Stewart
Summary The aim if this study was to investigate the hypothesis that K‐RAS 4A is upregulated in a mineralocorticoid‐dependent manner in renal cell carcinoma and that this supports the proliferation and survival of some renal cancers. Expression of the K‐RAS in renal tumour tissues and cell lines was examined by real‐time PCR and Western blot and mineralocorticoid receptor, and its gatekeeper enzyme 11β‐hydroxysteroid dehydrogenase‐2 was examined by immunocytochemistry on a tissue microarray of 27 cases of renal cell carcinoma. Renal cancer cells lines 04A018 (RCC4 plus VHL) and 04A019 (RCC4 plus vector alone) were examined for the expression of K‐RAS4A and for the effect on K‐RAS expression of spironolactone blockade of the mineralocorticoid receptor. K‐RAS4A was suppressed by siRNA, and the effect on cell survival, proliferation and activation of the Akt and Raf signalling pathways was investigated in vitro. K‐RAS4A was expressed in RCC tissue and in the renal cancer cell lines but K‐RAS was downregulated by spironolactone and upregulated by aldosterone. Spironolactone treatment and K‐RAS suppression both led to a reduction in cell number in vitro. Both Akt and Raf pathways showed activation which was dependent on K‐RAS expression. K‐RAS expression in renal cell carcinoma is at least partially induced by aldosterone. Aldosterone supports the survival and proliferation of RCC cells by upregulation of K‐RAS acting through the Akt and Raf pathways.